Perancangan Enterprise Arsitektur Menggunakan Framework Togaf - Ricky Anderson; Johanes Fernandes Andry (ULTIMA InfoSys, 2021)
Implementation of IS / IT (Information Systems) / (Information Technology) is indispensable in a business process when a organizations wants to grow bigger, and its operational level is getting less simple, so instructions on data, technology, and application functionality will also be increasingly needed. PT Ikido Jorr Indo Sepatu is a manufacturing company that produces shoes for babies, and toddlers. The authors find problem such as most of its business processes still do not take full advantage and not optimally using IS and IT, and sometimes problems in the form of human errors, such as writing wrong memos, wrong data entry, and not having “real time” data processing between each of company division that can interfere with ongoing business processes. Therefore the authors will design a company enterprise architecture (EA) that results in harmony between IS / IT and the business needs of PT Ikido Jorr Indo Sepatu. In this study, the authors will design the EA using TOGAF (The Open Group Architecture Framework) with the ADM (Architecture Development Method) method. The results of this study are in the form of a enterprise architecture blueprint for the TOGAF method that is adapted to the business processes that are running at PT. Ikido Jorr Indo Sepatu which can help maximize the company's growth. Index Terms—enterprise architecture; TOGAF ADM; PT Ikido Jorr Indo Sepatu